2019
DOI: 10.1021/acs.jpca.9b00877
|View full text |Cite
|
Sign up to set email alerts
|

Simple Flux-Side Formulation of State-Resolved Thermal Reaction Rates for Ring-Polymer Surface Hopping

Abstract: Employing the recently developed isomorphic Hamiltonian framework for including nuclear quantum effects in mixed quantum-classical non-adiabatic dynamics, we present a flux-side formulation of state-resolved thermal reaction rates for ring-polymer surface hopping (iso-RPSH). An appealing aspect of the new approach is that calculation of multiple stateresolved non-adiabatic thermal reaction rates is enabled with only a single free-energy surface calculation, whereas previous non-adiabatic flux-side formulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…The same analyses we have done in this work can be easily generalized and incorporated into those alternative ET rate theories to describe PMET processes. Here, we only briefly mention some of these theories: (i) to incorporate nuclear quantum effects from high-frequency vibrational modes, one can explicitly include the quantized vibrational states by using the Jortner theory, [125][126][127] or using the linearized path-integral Fermi's golden rule (FGR) rate expressions, [128][129][130] the state-dependent imaginary-time path integral approaches, [131][132][133][134][135] or the state-dependent Instanton theory, [136][137][138] (ii) to obtain accurate rate from the weak to strong electronic coupling regimes, one can use the state-dependent Instanton theory, 136,138,139 or compute rate through the fluxside correlation function 140 using linearized pathintegral approach, 141,142 state-dependent ringpolymer rate approaches, 133,134 or mixed quantumclassical approaches, [143][144][145][146][147][148][149][150] (iii) to incorporate memory effects of the bath, one can use the Zusman theory 151 that provides accurate non-markovian and non-adiabatic ET rate, [151][152][153][154] or use the linearized path-integral FGR rate expressions, [128][129][130] (iv) to treat non-equilibrium initial condition, one can employ the recently developed non-equilibrium FGR rate theory…”
Section: Polariton Mediated Electron Transfermentioning
confidence: 99%
“…The same analyses we have done in this work can be easily generalized and incorporated into those alternative ET rate theories to describe PMET processes. Here, we only briefly mention some of these theories: (i) to incorporate nuclear quantum effects from high-frequency vibrational modes, one can explicitly include the quantized vibrational states by using the Jortner theory, [125][126][127] or using the linearized path-integral Fermi's golden rule (FGR) rate expressions, [128][129][130] the state-dependent imaginary-time path integral approaches, [131][132][133][134][135] or the state-dependent Instanton theory, [136][137][138] (ii) to obtain accurate rate from the weak to strong electronic coupling regimes, one can use the state-dependent Instanton theory, 136,138,139 or compute rate through the fluxside correlation function 140 using linearized pathintegral approach, 141,142 state-dependent ringpolymer rate approaches, 133,134 or mixed quantumclassical approaches, [143][144][145][146][147][148][149][150] (iii) to incorporate memory effects of the bath, one can use the Zusman theory 151 that provides accurate non-markovian and non-adiabatic ET rate, [151][152][153][154] or use the linearized path-integral FGR rate expressions, [128][129][130] (iv) to treat non-equilibrium initial condition, one can employ the recently developed non-equilibrium FGR rate theory…”
Section: Polariton Mediated Electron Transfermentioning
confidence: 99%
“…By analyzing the rate constants for charge transfer between two ethylene-like molecules in a bath of Ne atoms we have shown that nuclear quantum effects are not of major importance at 300 K but become significant at lower temperatures. In future, we intend to compare the rate constants calculated with reactive flux formulation [71][72][73] with the rate constants computed here. Additionally, we aim at studying the temperature dependence of charge transport in more realistic systems, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It does share the single most important feature of standard adiabatic RPMD, in that it obeys quantum detailed balance by construction (provided a MQC method with this property is used). 1,2 We also expect that iso-RPMD will be accurate for systems in which the non-adiabatic transition is effectively classical and nuclear quantum effects are important for crossing a barrier away from this transition. In fact, the accuracy of iso-RPMD has already been demonstrated in such a situation by Tao et al in their calculation of state-resolved reaction rates for a one-dimensional two-state model of the F + H 2 reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the accuracy of iso-RPMD has already been demonstrated in such a situation by Tao et al in their calculation of state-resolved reaction rates for a one-dimensional two-state model of the F + H 2 reaction. 1,2 Application of the method to similar but more complex systems will no doubt provide physical insight in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation